Estimating dredging volume at sunda pondok dayung dock using s-convex function-based curve fitting to ensure indonesian navy ship safety - Ole, Yesaya Putra Dappa; Al Hazmy, Sofihara; Harist, Jiyaad Muhamad; Abdurrazzaq, Achmad (Desimal: Jurnal Matematika, 2025)
This study investigated the application of s-convex function-based curve fitting for estimating the dredging volume at Sunda Pondok Dayung Dock to ensure the safety of Indonesian Navy vessels. The research aimed to develop an alternative method to conventional numerical integration techniques by employing s-convex curve fitting using both two-point and three-point approaches and by comparing its performance with the trapezoidal rule, Simpson’s 1/3 rule, and Simpson’s 3/8 rule. Data from Pushidrosal’s 2023 survey were utilized, and explicit analytical forms for definite integral estimation were derived by approximating the function with s-convex methods. The results demonstrated that although the trapezoidal method produced the smallest relative error, the s-convex approach yielded a comparable error margin, differing by only 0.038%, which indicated its viability as an alternative method for dredging volume estimation. Future research was suggested to extend s-convex curve fitting to more than three points to further improve accuracy.